The Practice of Public Speaking with the Experiential Learning to Improve Self-Efficacy in Students of Islamic Boarding High School - Najlatun Naqiyah (Sociometry Journal of Social Science, Art and Humanity, 2022)
The industrial era 4.0 requires students to adapt well to have confidence in their own abilities, to have courage to come up in public, to convey ideas and to use technology for the sake of their welfare. This research aims at studying the application of students’ public speaking skills with the experiential learning method. There were 20 students participating in a training on public speaking at the Boarding School in East Java, for 6 months. In the public speaking practice, a student did it directly while the others observed the student doing the speech. There were four steps in the experiential learning method used this research: practice, reflection, improvement and follow-up. This research uses the qualitative method. The data were collected through observations and documentation. The results of the observations are supported by the students’ progress journals for those 6 months. The results of the public speaking through the experiential learning method indicate increased self-efficacy of the students, which further improves their abilities, performance and attitudes. The implication of this finding is that the experiential learning method can be used to improve students’ self-efficacy. Furthermore, students need to practice in front of their peers to eventually discover and recognize their own speaking style and attitude in public.